GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TERHADAP BAHAYA ASAP ROKOK - ADHA AGUNG WIJAYA SAPUTRA (Jurnal Medika Hutama, 2021)
Smoking is a form of tobacco use. The prevalence of smoking in Indonesia is 29%. Smoking has a major influence in damaging health. During pregnancy exposure to cigarette smoke has a negative impact on health. Cigarette exposure also affects the health of pregnant women and the fetus they contain, hindering the distribution of nutrients from mother to fetus. The purpose of this study was to determine the level of knowledge of pregnant women on the dangers of cigarette smoke. The method used in this research is a literature review study. Searching for library sources used through the website of the Ministry of Health, WHO, NCBI, Google Scholar. It can be concluded that the level of knowledge of pregnant women about the dangers of cigarette smoke for pregnancy is still high enough so that it is still necessary to increase the knowledge of pregnant women about the dangers of cigarette smoke.